Implementasi Perda Kabupaten Gianyar tentang Retribusi Izin Mendirikan Bangunan terhadap Bangunan Pariwisata di Kabupaten Gianyar - Putri Amelia Meirini; Wayan Wesna Astara; I Nyoman Sutama (Jurnal Interpretasi Hukum, 2020)
Every founder of a tourism building in Gianyar Regency is required to have a Building Permit (IMB) and pay the levies according to the regional government (Bupati) of Gianyar Regency. The government establishes a procedure for the construction of tourism buildings because they are one of the business fields of providing accommodation which is supervised by the Supervisor of the Investment Service and One Stop Integrated Service of the Gianyar Regency area who is appointed by the Regent and employees who are assigned certain tasks in the area of ​​regional retribution according to applicable legal rules. The issues the present examines are the legal arrangement for permits for the construction of tourism buildings in Gianyar regency and the implementation procedures for the Gianyar Regency Regional Regulation Number 14 of 01 concerning Building Permit Retribution, especially for tourism buildings in the district. The type of research used is the empirical research, which requires the researcher to collect data by coming to the research locus which is in the One Stop Investment and Integrated Service Office and the Civil Service Police Unit Office (Satpol PPl) of Gianyar. The results of the study reveal that the permit to construct tourism buildings is granted by the local government through the application process for building a tourism building permit which must follow the principles of prime and affordable service in accordance with Regional Regulation No. 14 of 01. Law enforcement in granting building permits and paying IMB levies in Gianyar Regency is executed out by giving sanctions to legal entities or building owners who violate the applicable regulations.